Legal insider - probate & administration of estate - UiTM, Faculty of Law (Faculty of Law, 2019)
A will is a declaration of a man's mind as to the proper disposition of his property after death. As such, a person who owns property during his lifetime has the power to direct its disposition after his death (Weisbord, Reid Kress, 2012). In the making of wills, the testator is the owner of the property and is granting the power to determine his successors in ownership (Gulliver, Ashbel G., and Catherine J. Tilson, 1941; Leslie, Melanie B., 1996). However, a will has no legal effect until the death of the testator, and it must be made in writing. In contrast, a privileged will is an informal will. The right to make a privileged will is only granted to soldiers and airmen "in actual military service" and sailors (which include mariners, seamen and members of the naval forces of Malaysia) while "being at sea". They are given the right to make a will in the best way they can without observing the formalities because of the imminent dangers, diseases, disasters, and sudden deaths, which may befall them during "actual military service" and while "being at sea" (Faridah Hussain, 2019). The underlying reason for the preservation of privileged will is the imminent dangers, diseases, disasters and sudden deaths, constantly faced by soldiers and sailors (Crowley, Wallace E.,1918). Hence, this immunity is granted by almost all jurisdictions, to this class of persons (Proffatt, John, 1876). Historically, soldiers have had free power to make a will temporarily in the best way that they can since the time of Julius Ceasar (Gillis, Edward, 1914). The term "in the best way" is well illustrated in the case of Re Stable Dalrymple v. Campbell [1918-19) All ER 299. In this case, the deceased, while under orders to leave for France, said to the plaintiff, in the presence of an independent witness: "If I stop a bullet everything of mine will be yours." The Probate, Divorce and Admiralty Division's Court held that the words used by the deceased were deliberately intended to give expression of his wishes as to what should be done with his property in the event of his death and constituted a valid soldier's will. In this case, Horridge J. pronounced for probate of the oral declaration as a will. In Malaysia, a privileged will can be made by declaration or disposition, oral or in writing (section 26(2) of the Wills Act 1959) as long as the testator has the testamentary intention expressed by such declaration (section 26(3) of the Wills Act 1959). It is not necessary for a privileged will to comply with the formalities, and it is not needed to be signed by the testator (section 26(4) of the Wills Act 1959).